Late Glacial-Postglacial Foraminiferal Boundary in Sediments of Eastern Canada, Denmark and Norway - Vilks, Gustavs (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1981)
Summary Sediments in cores collected from theScotian and Labrador shelves contain afaunal discontinuity where older benthicforaminiferal assemblages dominated byElphidium excavatum f. clavata change tomore diverse present day continentalshelf assemblages. A similar change isfound in Late Quaternary borings inDenmark (Jutland) and in the Oslofjordarea of Norway. The ,4C age of the faunalbreak varies from 10,000 years B.P. in theEuropean sediments to 13,000 years B.P.on the Scotian Shelf and 15,000 yearsB.P. on the Labrador Shelf. The present day océanographie settingalong the coasts of Norway, Denmarkand eastern Canada was establshedwhen the glacial ice retreated inland. Thedominance of E. excavatum f. clavata inthe older sediments is related to dilutedand cold coastal waters during the timewhen continental ice was ablating on theinner shelf. The disappearance of E,excavatum f. clavata therefore can beused to estimate the Late Glacial-Postglacial boundary in the Canadianand Scandinavian North Atlantic contin-ental shelf sediments. This paper reviewsthe evidence of the faunal break to alertgeologists in its possible use.